2021
DOI: 10.1002/ppsc.202100009
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives of Using Chitosan, Silver, and Chitosan–Silver Nanoparticles against Multidrug‐Resistant Bacteria

Abstract: materials are typically developed at a critical length of under 100 nm. However, other phenomena, such as transparency and stable dispersion, can occasionally extend the upper limit, and the use of the prefix "nano" is accepted for dimensions smaller than 500 nm. [2] Two relevant factors differentiate nanomaterials from macroscopic materials: first, the quantum effect that can promote changes in physical properties, such as color and electrical conductivity, and second, the surface effect related to the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 177 publications
(289 reference statements)
0
14
0
Order By: Relevance
“…The MBC of Arthrobacter bangladeshi MAHUQ-56 T -mediated synthesized AgNPs for both S. typhimurium and Y. enterocolitica was 12.5 ug/mL (Figure 9, Table 6). This MBC value was also significantly lower that of some other antibacterial agents against both S. typhimurium and Y. enterocolitica [47][48][49][50].…”
Section: Mic and Mbc Investigationmentioning
confidence: 87%
See 1 more Smart Citation
“…The MBC of Arthrobacter bangladeshi MAHUQ-56 T -mediated synthesized AgNPs for both S. typhimurium and Y. enterocolitica was 12.5 ug/mL (Figure 9, Table 6). This MBC value was also significantly lower that of some other antibacterial agents against both S. typhimurium and Y. enterocolitica [47][48][49][50].…”
Section: Mic and Mbc Investigationmentioning
confidence: 87%
“…Several studies reported that the MIC values of olive-oil polyphenol extract and Licochalcone A against S. Typhimurium were 625 and 62.5-1000 ug/mL, respectively [47,48]. Similarly, the MIC values of chitosan nanoparticles and Parrotia persica leaf extract against Y. enterocolitica were 1500 and 750 ug/mL, respectively [49,50]. MBC is the lowest concentration of antimicrobial agents that fully kills the tested pathogens.…”
Section: Mic and Mbc Investigationmentioning
confidence: 99%
“…Due to electronic, optical, and magnetic properties, multi-metallic nanoparticles were recently proposed as innovative antimicrobial agents, which could help to overcome antimicrobial resistance [ 32 ]. Chitosan and Chitosan/Ag NPs were also proposed as promising alternatives to overcome antimicrobial resistance in medical devices [ 33 ].…”
Section: Enhancement Of Antimicrobial Properties Via Nanomodification Of Epoxiesmentioning
confidence: 99%
“…POM microfiber is a well-investigated type of composite microfiber with excellent tensile strength to be used as framework to support β-CDs. The hydrophobic cavity of CDs allows them to form host-guest complexes with Ag nanoparticles in POM [18][19][20][21]. And to the best of our knowledge, the preparation of Ag/POM/β-CD composite microfiber matrices using electrospinning has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%